Physiological Basis for Glyphosate Tolerance in Hard Fescue and Perennial Ryegrass Cultivars. Issue 5 (1st September 2015) - McCullough, Patrick E.; Yu, Jialin; Shilling, Donn G.; Czarnota, Mark A.
ABSTRACT: Glyphosate effectively controls susceptible biotypes of numerous weed species, but applications are often injurious to turfgrass. 'Aurora Gold' hard fescue ( Festuca longifolia Thuill.) and 'JS‐501' perennial ryegrass ( Lolium perenne L.) have enhanced tolerance to glyphosate compared with traditional varieties, but the mechanisms that convey tolerance are not well understood. The objectives of this research were to investigate the physiological basis for glyphosate tolerance in Aurora Gold hard fescue and JS‐501 perennial ryegrass. In greenhouse experiments, the estimated glyphosate rate required to reduce dry shoot mass 50% from the nontreated shoots at 4 wk after treatment measured >3360, >3360, 1850, and 1310 g acid equivalent (a.e.) ha −1 for Aurora Gold, JS‐501, 'Manhattan V' perennial ryegrass, and 'Stonehenge' hard fescue, respectively. Absorption of 14 C‐glyphosate was similar between hard fescue cultivars and averaged 5% of the applied radioactivity. However, Aurora Gold accumulated 20% less shikimate than Stonehenge when incubated at ≥250 μM of glyphosate in leaf disk assays. JS‐501 perennial ryegrass absorbed less 14 C‐glyphosate than Manhattan V (13 vs. 22% of the applied) and accumulated ∼50% less shikimate. All cultivars translocated the majority of absorbed radioactivity out of the treated leaf. Based on these findings, glyphosate has less target‐site inhibition in Aurora Gold compared with a more susceptible hard fescue cultivar. The glyphosate tolerance of JS‐501 perennial ryegrass involves two mechanisms including less absorption and target‐site inhibition from a more susceptible cultivar.